Jacek Hadryś, Dynamika chrześcijańskiego życia duchowego, „Studia i Materiały”, Wydział Teologiczny UAM, Poznań 2017, s. 297. - Cichosz, Wojciech (Studia Gdańskie, 2021)
Jacek Hadryś, Dynamika chrześcijańskiego życia duchowego, „Studia i Materiały”, Wydział Teologiczny UAM, Poznań 2017, s. 297.